Analisis Pengaruh Inflasi terhadap Kebijakan Fiskal di Provinsi Banten - Haniva, Sophia Al; Awalunnisa, Yuli; Putri, Tria Damayanti; Sakhi, Rakha Fairuz (PT PUSTAKA CENDEKIA GROUP, 2023)
In a country, it is normal for a country to have dynamics or turmoil in every sector, especially in the economic sector. The economic sector in every country can be said to be at risk, because the economy is like the tides and ebbs of the sea, due to economic turmoil that is not always stable. In the province of Banten there was an economic upheaval in several consumption goods such as food, beverages and tobacco. In 2010 the increase in inflation was mainly driven by an impact on rising food prices in general, continuing in 2011 and 2012 the rate of inflation was controlled because of the strategy carried out by the government by fulfilling the supply and distribution of food. Furthermore, in 2013 and 2014, the inflation rate increased again, this is dominated by global economic problems that affect the increase in energy and food prices in international markets. The government took firm steps, by implementing energy reform policies in an effort to ease the tax burden and reallocate the supporting expenditure budget to a more productive expenditure budget. Furthermore, in 2015-2016, inflation was successfully suppressed by the government supported by the stability of the rupiah exchange rate which was a factor in controlling the inflation rate this year. Likewise in 2017, the inflation rate remained under control, this was supported by controlled prices, demand and supply. Furthermore, in 2019-2020 the inflation rate was still under control until the Covid outbreak hat attacked Indonesia also had an impact on Indonesia's Economic Inflation. Based on the monitoring results of BPS Banten Province, inflation of 1.12% increased from the Consumer Price Index (CPI) of 111.58 in August 2022 to 112.84 in September 2022. In September 2022, September 2022 inflation was 4.85. 5.86%. In 2022, the inflation rate is expected to meet the inflation target. The government together with Bank Indonesia have a strategy and concept in an effort to deal with inflation. There are 4K concepts of strategy, including affordability, delivery availability, smooth distribution and effective communication.